Impact of prophylactic gastrostomy or reactive NG tube upon patient-reported long term swallow function following chemoradiotherapy for oropharyngeal carcinoma: A matched pair analysis. (August 2016) - Sethugavalar, Brinda; Teo, Mark T.; Buchan, Catriona; Ermiş, Ekin; Williams, Gillian F.; Sen, Mehmet; Prestwich, Robin J.D.
Highlights: Influence of prophylactic gastrostomy on long term swallow outcomes is uncertain. Study of patient-reported long term swallow outcomes following chemoradiotherapy. Matched pair analysis used to assess influence of route of enteral feed. Reactive nasogastric feed associated with superior long term swallow outcomes. Summary: Objectives: The purpose of this matched pair analysis is to assess patient-reported long term swallow function following chemoradiotherapy for locally advanced oropharyngeal cancer in relation to the use of a prophylactic gastrostomy or reactive nasogastric (NG) tube. Materials and methods: The MD Anderson Dysphagia Inventory (MDADI) was posted to 68 consecutive patients with stage III/IV oropharyngeal squamous cell carcinoma who had completed parotid sparing intensity modulated radiotherapy with concurrent chemotherapy between 2010 and 2012, had not required therapeutic enteral feeding prior to treatment, minimum 2 years follow up post treatment, and who were disease free. 59/68 replies were received, and a matched pair analysis (matching for T and N stage) was performed for 52 patients, 26 managed with a prophylactic gastrostomy and 26 with an approach of an NG tube as needed. Results: There were no significant differences in patient demographics, pre-treatment diet and treatment factors between the two groups. Patient-reported swallowing function measured using the MDADI was superior for patients managed with an NG tube as required compared with a prophylactic gastrostomy: overall composite score 68.1 versus 59.4 ( p = 0.04), global score 67.7 versus 60 ( p = 0.04), emotional subscale 73.5 versus 60.4 ( p < 0.01), functional subscale 75.4 versus 61.7 ( p < 0.01), and physical subscale 59.6 versus 57.1 ( p = 0.38). Conclusions: Compared with an approach of an NG tube as required, the use of a prophylactic gastrostomy was associated with inferior long term patient-reported long term swallow outcomes.